PELATIHAN MANAJEMEN PERPUSTAKAAN UNTUK MENINGKATKAN MINAT BACA DI RPTRA DHARMA SUCI, PEJAGALAN, JAKARTA UTARA - Yustinus Yuniarto (Universitas Bunda Mulia, 2017)
One of the main elements in the Tri Dharma Perguruan Tinggi is carrying out community service activities. Public Space Integrated Child Friendly (RPTRA) were built and developed by Jakarta Provincial Government has a library that needs to be managed properly. To increase interest in reading among library users, especially children, the Program Management Studies Bunda Mulia University, held a traning program in the library management and also held activities in order to increase interest in reading. The educational background or knowledge of the librarians of RPTRA who are not educated libraries of course make them limited in managing the library including developing activities related to the development of reading interest. Through the training of good library management to increase interest in reading is seen some things that can be felt directly by the librarians and the children as the majority of library users in RPTRA Dharma Suci. For the board perceived the benefits of knowledge about how to manage the library well. Then also gain knowledge on how to develop activities that can be used to develop reading interest among library users, especially children. For children as library users it is felt that through the example of storytelling activities, their interest in finding other stories through library collection books in RPTRA Dharma Suci can increase. This is certainly positive because it will make them spend more time in the library than playing on the streets. So therefore, the future of these children can continue to develop themselves in order to improve their welfare in the future.Keywords: management, library, reading interest, welfare living